Информационное право: учебное пособие / М. М. Рассолов - Рассолов Михаил Михайлович (Institutiones, 1999)
Экземпляры: СЭ (20000731) / Инвентарный номер: 1036182 / Цена: 49.00 / Сис.шифр: 67.401 / Авт.знак: Р 24 / ГРНТИ: 10 / ББК: 67.401.114